Glycosyltransferases within the psrP Locus Facilitate Pneumococcal Virulence - Middleton, Dustin R. (J Bacteriol, 2021)
The pneumococcal serine-rich repeat protein (PsrP) is a high-molecular-weight, glycosylated adhesin that promotes the attachment of Streptococcus pneumoniae to host cells. PsrP, its associated glycosyltransferases (GTs), and dedicated secretion machinery are encoded in a 37-kb genomic island that is present in many invasive clinical isolates of S. pneumoniae. PsrP has been implicated in establishment of lung infection in murine models, although specific roles of the PsrP glycans in disease progression or bacterial physiology have not been elucidated. Moreover, enzymatic specificities of associated glycosyltransferases are yet to be fully characterized. We hypothesized that the glycosyltransferases that modify PsrP are critical for the adhesion properties and infectivity of S. pneumoniae. Here, we characterize the putative S. pneumoniae psrP locus glycosyltransferases responsible for PsrP glycosylation. We also begin to elucidate their roles in S. pneumoniae virulence. We show that four glycosyltransferases within the psrP locus are indispensable for S. pneumoniae biofilm formation, lung epithelial cell adherence, and establishment of lung infection in a mouse model of pneumococcal pneumonia. IMPORTANCE PsrP has previously been identified as a necessary virulence factor for many serotypes of S. pneumoniae and studied as a surface glycoprotein. Thus, studying the effects on virulence of each glycosyltransferase (GT) that builds the PsrP glycan is of high importance. Our work elucidates the influence of GTs in vivo. We have identified at least four GTs that are required for lung infection, an indication that it is worthwhile to consider glycosylated PsrP as a candidate for serotype-independent pneumococcal vaccine design.